2018
DOI: 10.24912/jmishumsen.v2i1.1688
|View full text |Cite
|
Sign up to set email alerts
|

Prestasi Akademik Ditinjau Dari Keterlibatan Remaja Dalam Kegiatan Ekstrakurikuler

Abstract: Kegiatan ekstrakurikuler merupakan kegiatan yang dilakukan di luar jam pelajaran untuk memperluas wawasan pengetahuan yang telah dimiliki dari berbagai bidang studi. Penelitian ini bertujuan untuk melihat hubungan antara kegiatan ekstrakurikuler dengan prestasi akademik pada mahasiswa. Jumlah subjek pada penelitian ini adalah 640 orang. Subjek diambil dengan menggunakan teknik acidental sampling, yaitu jenis sampling nonprobabiliti yang melibatkan sampel diambil dari bagian populasi yang dekat dengan sumber da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This is part of academic achievement, if individuals can optimally try to achieve these things during their studies at university (Lubis & Aditiya, 2023). Academic achievement is a term that refers to the results of a person's achievements in accordance with his goals in the academic field, and the success of his efforts in studying optimally, the results obtained are in the form of grades and numbers or symbols (Agusti & Rahmadhani, 2020;Iryanti, 2014;Mardelina & Muhson, 2017;Setiawan, 2000;Umamah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is part of academic achievement, if individuals can optimally try to achieve these things during their studies at university (Lubis & Aditiya, 2023). Academic achievement is a term that refers to the results of a person's achievements in accordance with his goals in the academic field, and the success of his efforts in studying optimally, the results obtained are in the form of grades and numbers or symbols (Agusti & Rahmadhani, 2020;Iryanti, 2014;Mardelina & Muhson, 2017;Setiawan, 2000;Umamah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that participation in extracurricular activities outside of the classroom, such as student organizations, clubs, and social events, can help students become more engaged in their studies and improve their academic performance. Additionally, the support that students receive from campus lecturers and staff members plays an important role in increasing student engagement as well as the academic achievement of those students (Umamah, Anggraini, Edyta, & Faradiba, 2018). Participation in extracurricular activities has positively impacted student engagement and academic performance.…”
Section: Introductionmentioning
confidence: 99%